Boy crazy - Abbott, Hailey (New York New York, NY : HarperTeen, 2009)
"Cassie and her two best friends, Greta and Keagan, are so over boyfriends. But just because the girls are anti- boyfriend doesn't mean they're anti-boy. So, they make a pact for the summer: They'll each kiss ten different guys before school starts--no commitments, no drama, just fun. Sounds easy enough. Then Cassie meets the perfect guy(nine boys too soon), and the pact starts to seem like a terrible idea"--P. [4] of cover.
Requires Adobe Digital Editions (file size: 1348 KB) or Adobe Digital Editions (file size: 402 KB) or Mobipocket Reader (file size: 195 KB).
Keywords: Dating (Social customs) -- Juvenile fiction; Friendship -- Juvenile fiction; Dating (Social customs) -- Fiction; Friendship -- Fiction; Electronic books